Conhecimento e percepção de graduandos em enfermagem sobre precauções para prevenção de transmissão de microrganismos - Silva, Darlyani Mariano da (Universidade Federal de São Carlos, 2023)
Health Care-Related Infections (HAIs) represent one of the major public health problems in the world, which makes it urgent to reduce their spread through adherence by health professionals to standard and specific precautionary measures. In general, the experience of the COVID-19 pandemic brought up the discussion on the transmission of microorganisms, and adherence to precautionary measures by professionals in different health care settings. In this context, questions also arise about how this topic has been addressed in nursing education, considering the relevance of this future professional in actions to prevent and control the transmission of microorganisms, whether they are related to health care or in the community. Thus, the present study aimed to identify the knowledge and perception of undergraduate nursing students about standard precautions (SP) and specific precautions (SP) to prevent the transmission of microorganisms. The realization of this project provides a standardized instrument, validated by specialists, with a CVI above 0.78 in all items. This is a specific instrument for undergraduate nursing students, consisting of three domains, namely knowledge about SP and specific precautions (SP); students' perception of their practice and characterization of teaching on the subject. The study included 582 undergraduate nursing students from all regions of Brazil, mostly women 82.6% (n=481) with a mean age of 27 years. In the PE theme, doubts were identified in the concepts of droplet precaution by 55.8% (n=325) and aerosols by 42.6% (n=248) of the participants. It was mentioned, by most of the students, 86.4% (n=503), that the emergence of COVID-19 influenced their interest in the subject of precautions and that 557 (95.70%) feel confident about how and when they should clean the hands. Regarding the approach to the PE and PP theme, 48.8% (n=284) reported being addressed in an exclusive discipline. The situational diagnosis carried out identified that the knowledge and perception of undergraduate nursing students about PP and PE measures to prevent the transmission of microorganisms are below adequate. The knowledge of undergraduate nursing students does not include the general infection prevention and control measures necessary to produce quality and safe care for patients and professionals. Thus, this study is expected to contribute to the training of future nurses by listing the essential elements to be addressed in their training.
Knowledge and perception of undergraduate nursing students about precautions to prevent the transmission of microorganisms
Keywords: Transmissão de doença infecciosa; Estudo de validação; Educação em enfermagem; Controle de infecções; Precauções universais; CIENCIAS DA SAUDE::ENFERMAGEM